PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN (Survei pada Mahasiswa Pengguna Gojek di Universitas Slamet Riyadi Surakarta) - Akmal Muhammad Fauzan; Sumaryanto Sumaryanto; Retno Susanti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2021)
The purpose of this study was to analyze the significance of the effect of service quality and price on consumer satisfaction of Gojek users. This research is a survey of students of the University of Slamet Riyadi who use Gojek. The study population was an unknown number of consumers using Gojek, Slamet Riyadi University students. A sample of 100 people with a purposive sampling technique. Data collection techniques using kueisoner, observation and literature study. The data analysis technique used multiple linear regression. The results showed that service quality had a significant effect on customer satisfaction. Price has a significant effect on customer satisfaction.